2001
DOI: 10.1002/mds.1143
|View full text |Cite
|
Sign up to set email alerts
|

Idazoxan, an alpha‐2 antagonist, and L‐DOPA‐induced dyskinesias in patients with Parkinson's disease

Abstract: Dyskinesia is a frequent and disabling side effect in patients with Parkinson's disease treated with chronic dopa-therapy. Preclinical data in the 1-methyl-4-phenyl-1,2,3,6,-tetrahydropyridine (MPTP) monkey suggest that alpha-2 antagonists may reduce dihydroxyphenylalanine (L-DOPA)-induced dyskinesia. We assessed, in a pilot randomised placebo-controlled study, the effects of single oral doses (10 mg, 20 mg, and 40 mg) of idazoxan, an alpha-2 antagonist, on motor parkinsonian disability and L-DOPA-induced dysk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 30 publications
0
88
0
Order By: Relevance
“…The selective a 2 -receptor antagonist fipamezole also alleviated LID while enhancing L-DOPA antiparkinsonian efficacy in the MPTP-lesioned common marmoset (Savola et al, 2003) and the MPTP-lesioned macaque (Johnston et al, 2010c). At the clinical level, idazoxan effectively alleviated LID (Rascol et al, 2001a) but had no effect on apomorphine-induced dyskinesia (Manson et al, 2000), whereas fipamezole was also effective at relieving LID (Dimitrova et al, 2009;Lewitt et al, 2012).…”
Section: Adrenergic Neurotransmissionmentioning
confidence: 99%
“…The selective a 2 -receptor antagonist fipamezole also alleviated LID while enhancing L-DOPA antiparkinsonian efficacy in the MPTP-lesioned common marmoset (Savola et al, 2003) and the MPTP-lesioned macaque (Johnston et al, 2010c). At the clinical level, idazoxan effectively alleviated LID (Rascol et al, 2001a) but had no effect on apomorphine-induced dyskinesia (Manson et al, 2000), whereas fipamezole was also effective at relieving LID (Dimitrova et al, 2009;Lewitt et al, 2012).…”
Section: Adrenergic Neurotransmissionmentioning
confidence: 99%
“…These include the opioid system, which acts as a modulator of dopamine and a cotransmitter within GABAergic neurons (Fox et al 2006;Hallett and Brotchie 2007), the adenosine system (Calon et al 2004), the serotonergic system (Carta et al 2007;Carlsson et al 2009), and the a2 adrenergic system (Fox et al 2001;Rascol et al 2001). Piccini et al (1997) found reduced binding of [ 11 C]diphrenorphine (a nonselective marker of opioid receptors) in the striatum, thalamus, and anterior cingulate of PD patients with LID compared to without.…”
Section: Motor Complications Of Therapydyskinesiasmentioning
confidence: 99%
“…They also potentiate amphetamine-and apomorphineinduced rotations in unilaterally nigral lesioned rats (Mavridis et al, 1991;Chopin et al, 1999;Haapalinna et al, 2003), prolong the duration of L-DOPA-induced contralateral rotations (Haapalinna et al, 2003), have a potent effect on L-DOPA-induced dyskinesia, and can extend the anti-parkinsonian effect of L-DOPA in MPTP-treated monkeys (Henry et al, 1999;Domino et al, 2003). Incomplete pilot clinical trials suggest that, indeed, such class of drugs reduces bradykinesia and rigidity in parkinsonian patients (Brefel-Courbon et al, 1998) and dyskinesia severity when given in combination with L-DOPA (Brefel-Courbon et al, 1998;Rascol et al, 2001). Results from the double-blind placebo-controlled fipamezole clinical trial are still awaited.…”
Section: Clinical Relevancementioning
confidence: 99%